Implementasi Kurikulum 2013 pada Pembelajaran Kimia Di MA PP Syafa’aturrasul Teluk Kuantan - Rosa Murwindra; Nofri Yuhelman (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2019)
Abstract This study aims to determined the effectiveness of the curriculum 2013 implementation in the planning, implementation and evaluation system implemented in chemistry learning at MA PP Syafa’aturrasul Teluk Kuantan. This research is a type of qualitative research with a descriptive approach. The population in this study was MA PP Syafa’aturrasul Teluk Kuantan. Sampling refers to the purposive sampling technique. Data collection was obtained through interviews, participant observation, documentation and questionnaires. Respondents consisted of chemistry teachers, Waka. Curriculum and students. The validity of the data is obtained through triangulation of data sources and data retrieval techniques. The data analysis technique used is quantitative analysis using Guttman Scale analysis and qualitative analysis, namely the Miles and Huberman models. Based on the results of the study it can be concluded that the effectiveness of the 2013 curriculum in learning chemistry at MA PP Syafa’aturrasul Teluk Kuantan runs very effectively or very well. This can be seen from the acquisition of the percentage score of each aspect namely 100% planning aspect, 94% implementation aspect and 100% evaluation aspect, so that the average results of the overall aspects obtained are 96%. Keywords: Curriculum 2013, Students, Chemistry Learning, MA PP Syafa’aturrasul Teluk Kuantan